An autonomous vehicle for people with motor disabilities. - Bourhis, G.
The authors describe the creation of the VAHM prototype, including the hardware and software functionalities and other aspects of this ?smart? wheelchair
Keywords: VAHM; Autonomous vehicle; Handicapped aids; Hardware; Localisation; Navigation; Obstacle avoidance; Path planning; Smart wheelchair; Software